Glucocorticoid receptor upregulation increases radioresistance and triggers androgen independence of prostate cancer. Issue 12 (23rd July 2019) - Chen, Xiaodong; Chen, Feng; Ren, Yu; Weng, Guobin; Keng, Peter C.; Chen, Yuhchyau; Lee, Soo Ok
Abstract : Background: Despite the overall success of radiotherapy, a significant number of patients develop radioresistance, which leads to local regional recurrence and distant metastasis. We studied whether repeated radiation treatment promotes androgen‐independent survival of prostate cancer (PCa) cells and their metastatic potential. We also studied whether glucocorticoid receptor (GR) increase in radioresistant cells is associated with acquisition of these aggressive characteristics. Methods: Radioresistant LNCaP (LNCaPR18) and C4‐2 (C4‐2R26) PCa sublines were developed by repeated radiation treatments of parental cells. Levels and activations of androgen receptor (AR) and GR in radioresistant PCa cells and respective parental cells were investigated in quantitative real‐time polymerase chain reaction/Western blot analyses and immunofluorescence staining. Androgen‐independent survival of radioresistant cells was tested in in vitro cell growth assays and the castration‐resistant survival of these cell‐derived tumors were investigated in mouse xenografts. Results: Higher GR levels, but lower AR levels were detected in radioresistant cells than in parental cells. Radiation‐induced GR upregulation was associated with increased intracellular cyclic adenosine monophosphate. As a consequence of GR activation, LNCaPR18 cells survived well in an androgen‐depleted culture condition while parental cells could not. Results of in vivo mouse studies showed survival of LNCaPR18 cell‐derived tumors in castrated mice while parental cell‐derived tumors regressed. The growth of LNCaPR18 cell‐derived tumors in castrated mice was impaired when treated with the anti‐GR agent mifepristone. In experiments with C4‐2/C4‐2R26 cell sets, GR activation in C4‐2R26 cells increased their metastatic potential. Conclusion: GR activation in radioresistant cells mediates androgen independence and facilitates PCa progression.